INNOVATING MEDICAL SCIENCE FOR SUSTAINABLE HEALTH SOLUTION ANALYZING THE AYUSHMAN BHARAT SCHEME - Rani, Pooja; Kaur, Rupinder (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The paper attempts to analyses the multifaceted relationship between medical innovation and the implementation of government sponsored health insurance scheme ‘Ayushman Bharat- Pradhan Mantri Jan Arogya Yojana’ scheme in Achieving Sustainable Health outcomes. The study begins by describing the conceptual framework of medical innovation and sustainable health outcomes. Medical Innovation encompasses a spectrum of advancements, ranging from ground breaking discoveries in Pharmaceuticals and medical devices to transformative developments in healthcare delivery system and digital health technologies. Sustainable health outcomes on the other hand, encompasses the holistic wellbeing of individual and communities over time. It includes factors such as equitable access to healthcare, cost-effectiveness and environmental impact. The AB- PMJAY scheme launched by government of India in 2018 in all over the India. The scheme based on the motive of Universal Health Coverage (UHC), which has been implemented to meet sustainable development goals (SDGs) and following the commitment, “Leave No One Behind”. Its Ultimate aim is to achieve Sustainable health outcomes. The study examines the adoption of innovative medical technologies, treatments, and practices facilitated by the scheme, shedding light on their contributions to improved patient care, disease management, and overall healthcare sustainability on the basis of available data and previous studies. It is found in this analytical study that innovation in medical science like the use of AI in the medical field offers transformative opportunities to achieve sustainable health solutions by enhancing early disease detection, personalized treatment planning.